World Games Kaohsiung 2009 Beach handball torunament: Statistical analysis - König, O.; van de Vyle, J.; Meimaridis, I.; Gehrer, A. (2010)
The IHF Beach Handball Scouting System had its beginning before the Beach Handball World Championships 2008 in Cadiz (ESP). During this event, an explicit analysis of the game Beach Handball itself was done for the first time. The Scouting System was developed by Oliver König and Alexander Gehrer (member of the IHF`s Beach Handball Working Group) in the course of a final thesis submitted to the University of Tübingen (GER). With the development of this Scouting System, two main goals were achieved: I. The gained results are used as a basis for the development of the game and its rules, II. the results were immediately provided to the participating nations in this event. During the different steps of the development of the Scouting System, all provisional results were coordinated with the experts of the IHF`s Beach Handball Working Group. For every element to being scouted, detailed definitions were produced. To meet scientific requirements, the different quality criteria of scientific scouting were included. In the first test 2008, the Scouting was performed handwritten. For the World Games 2009 in Kaohsiung (TPE) the next step has been done. To improve the Scouting itself but first of all to make the analysis of the collected data easier and faster, the System was upgraded for usage on Touch-Screens. With this new technology the Scouting and the collection of the data is much easier but the most important advantage is, that an immediate, very fast and much more comprehensive evaluation of the results is possible.